DAILY BLOOD PRESSURE PROFILE AND HEART RATE VARIABILITY IN PATIENTS WITH ESSENTIAL HYPERTENSION - Kuzminova, N.V.; Romanova, V.O.; Ivankova, A.V.; Lozinsky, S.E.; Knyazkova, I.I.; Kedyk, I.O.; Shkarivsky, Yu.L. (World of Medicine and Biology, 2025)
This article presents the results of a study investigating changes in the daily blood pressure profile and heart rate variability in patients with stage II hypertension. The daily blood pressure profile was studied utilizing data acquired from daily blood pressure monitoring. Furthermore, heart rate variability, as an indicator of autonomic nervous system status, was investigated through the analysis of 5-minute cardiogram recordings. The study revealed that, in most patients with stage II hypertension, a disturbance exists in the daily blood pressure profile, characterized by either insufficient or excessive nocturnal reduction in blood pressure or, conversely, an elevation in nocturnal blood pressure. There was a tendency toward more frequent detection of nocturnal elevation of systolic blood pressure and excessive reduction of diastolic blood pressure in the subgroup of patients with stage 3 hypertension. In the presence of concomitant ischemic heart disease, daytime and nighttime diastolic blood pressure levels exceeded the corresponding indicators in patients with isolated hypertension. When assessing autonomic nervous regulation in patients with stage II hypertension, significant changes in its indicators were found relative to the control group, without a significant difference depending on the degree of hypertension, with the exception of a decrease in the standard deviation of the R-R interval and an increase in the LF/HF ratio in patients with stage III hypertension, which indicated an increase in the influence of the sympathetic branch of autonomic regulation. Thus, patients with stage II hypertension show an increase in the tone of the sympathetic branch of the autonomic nervous system, as evidenced by an increase in the proportion of pathological blood pressure profiles and changes in heart rate variability indicators.